New record, geographic variation and redescription of Apedilum elachistus Townes (Diptera: Chironomidae: Chironominae) - Donato, Mariano Humberto (2008)
Apedilum elachistus Townes 1945 is recorded from Argentina, representing the southernmost record of this species. Due to dissimilarities found between South and North American specimens a Principal Component Analysis and Minimum Spanning Tree were performed in order to determine if these differences reflect a geographic differentiation. The results show North–South variation in the number of acrostichal setae, number of dorsocentral setae, number of prealar setae, wing length, VR, length of thorax, and length of abdomen for males, and number of gonocoxite IX setae, length of thorax, number of temporal setae, length of palpomere III, wing length, BV2, length of notum, BV1, number of dorsocentral setae, length of palpomere IV, length of abdomen, VR, and length of palpomere V for females. Consequently, Apedilum elachistus is redescribed as larva, pupa, male, and female.